Active galaxies in the field and in Galaxy Clusters - Andreasyan, R. R.; Hakopian, S. A.; Mahtessian, A. P.; Sukiasyan, A. G.
We review the current activities of the Department of Active Galaxies of Byurakan Astrophysical Observatory. The studies include broad areas, ranging from manifestations of activity in our galaxy, other galaxies and clusters of galaxies to the study of magnetic fields, the formation of these fields, and cosmological questions.
Keywords: Galaxies